Perancangan dan Penerapan Sistem Informasi Akuntansi Berbasis Website Pada Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi’iyah - Sari Mujiani; Khoirunnisa Mardhiyah (AKRUAL : Jurnal Akuntansi dan Keuangan, 2019)
The purpose from this study is to create web-based accounting information system for administration matter in Faculty of Economy, Islamic University As-Syafi’iyah.In such way, with the creation of web-based accounting information system, it could give a good influence for administration matter in minimizing the error and also optimizing the administration activity. The web-based accounting information system includes the revenue cycle and expenditure cycle. Method used in analyzing the data is descriptive analytical study. The data are gained from interview and observation. Prototype approach is used for the system advancing method. The outcome of this study shows that web-based accounting information system could help in optimizing the administration activity and help to cope the drawback which happens in manual system